Diffusion of global climate policy: National depoliticization, local repoliticization in Turkey - BAYKAL FİDE, ECE (My University, 2023)
Although climate policy diffusion is widely studied, we know comparatively little about how these global policies and the norms that surround them are used by various political actors seeking to advance their own agendas. In this article, we focus on how global climate norms are diffused differently at national and local scales and used to repoliticize or depoliticize climate change. We focus on the case of Turkey, which carries the stark contrast of showing willingness to achieve global climate goals in the international arena but less so in domestic politics and actions. The article employs a novel methodological approach, using topic modeling and network analyses on a range of climate change–related policy documents, and interviews with high-level officers, conducted at the three jurisdictional levels in Turkey. The findings reveal that although global climate policy is diffused to both national and local governments, it is used in different ways at these levels. The national government uses climate policy diffusion to depoliticize climate change by creating ad hoc climate coalitions and limiting local climate actions to seeking external climate-related funds. Meanwhile, the metropolitan municipalities replicate nationally adopted climate goals, whereas the district municipalities domesticate ambitious climate norms and repoliticize climate change via local climate entrepreneurs and civic action. The paper contributes to understanding how climate policy diffusion and norm domestication can have different political outcomes in achieving global climate goals and argues for increased policy attention to the strategic use of climate policy diffusion for the depoliticization of climate change.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Policy diffusion; Norm domestication; Turkey; Depoliticization; Repoliticization; Local governments